LEVELS OF MALONDIALDEHYDE AND CALCITONIN GENE-RELATED PEPTIDE IN PULP INFLAMMATION DUE TO LPS INDUCTION DURATION - Nurhapsari, Arlina; Kusuma, Andina Rizkia Putri (Odonto : Dental Journal, 2022)
Background: Administration Lipopolysaccharide (LPS) to pulp tissue might produce inflammation. Inflammation occurs, which can lead to oxidative stress and neuropeptides release. Malondialdehyde (MDA) is an oxidative stress measure, while calcitonin gene-related peptide (CGRP) is a neuropeptide found in large amounts in the pulp. This study attempted to analyze levels of CGRP and MDA in LPS inflamed rat pulp tissueMethode: Wistar rats' maxillary incisors were treated to LPS stimulation. A total of 30 mice were separated into six groups, each with five animals. The groups were created by administering LPS to the pulp for 6, 12, 24, 48, and 72 hours. Rat without pulpal exposure (0 hour) served as controls. Enzyme-linked Immunosorbent Assay (ELISA) was used to measure the levels of MDA and CGRP in the pulp tissue.Result : MDA and CGRP levels were found to be significantly different in all groups (p0.05 mohon diberi keterangan apakah </>/=). With LPS administration, MDA levels increased on average, whereas CGRP levels fluctuated. Conclusion: The presence of inflammation in the pulp was shown by changes in MDA and CGRP levels after 6 hours of LPS injection. The effect of rising MDA levels on inflamed pulp tissue did not produce effects that were directly proportional to or vice versa with CGRP levels that showed fluctuated.